Modeling the pathways and attenuation of nutrients from domestic wastewater treatment systems at a catchment scale. (October 2016) - Gill, Laurence W.; Mockler, Eva M.
Abstract: Domestic Wastewater Treatment Systems (DWTS) are often cited as significant sources of pollution in rural catchments. A mass balance based model has been developed to determine annual nutrient loading from individual DWTS into rivers in Ireland. The transport and attenuation of nitrogen and phosphorus in DWTS effluent to groundwater and surface water has been formulated using the results from field research in Ireland, as well as being informed by other international studies. Conceptually the model splits the transport of nutrients to the river into three pathways: direct to surface water (for areas of inadequate percolation), a near surface (subsoil) pathway, and a groundwater pathway. The model quantifies the net nutrient contribution for each DWTS and has been incorporated into a broader source load apportionment catchment model which includes agricultural inputs, thereby enabling the relative risk of nutrient pollution from DWTS in a catchment to be defined. Highlights: Mass balance based model to determine annual nutrient loading from DWTS to rivers. Model splits the transport of nutrients to the river into three distinct pathways. Transport and attenuation of nutrients determined by local subsoil permeability. Model incorporated into a broader source load apportionment catchment model. Relative risk of nutrient pollution from DWTS in a catchment can be identified.